2011
DOI: 10.4068/cmj.2011.47.1.57
|View full text |Cite
|
Sign up to set email alerts
|

A Case of a Zotarolimus-Eluting Stent Fracture in the Left Anterior Descending Artery in a Patient Undergoing Hemodialysis

Abstract: Although stent fracture after implantation of a drug-eluting stent (DES) is a rare complication, it has been suggested to be a cause of restenosis. To date, most DES fractures have been associated with sirolimus-eluting stents. We describe here a case of a zotarolimus-eluting stent fracture after 8 months of stent placement in a calcified left anterior descending artery lesion in a patient undergoing hemodialysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
1
0
0
Order By: Relevance
“…They reported that stents with modular structure demonstrated better behavior than slotted tube ones in the tensile-compression fatigue test, and stents made of cobalt alloy had a longer endurance due to its better mechanical properties than stainless steel. In addition, clinical reporting of EN stent fracture is rare; to the best of our knowledge, it has been reported in only 3 cases [7][8][9]. These lines of available evidence strongly support the results of our study.…”
Section: Discussionsupporting
confidence: 89%
“…They reported that stents with modular structure demonstrated better behavior than slotted tube ones in the tensile-compression fatigue test, and stents made of cobalt alloy had a longer endurance due to its better mechanical properties than stainless steel. In addition, clinical reporting of EN stent fracture is rare; to the best of our knowledge, it has been reported in only 3 cases [7][8][9]. These lines of available evidence strongly support the results of our study.…”
Section: Discussionsupporting
confidence: 89%